FERMENTASI BIOETANOL DARI NIRA NIPAH KENTAL SECARA SEMI SINAMBUNG DENGAN PENAMBAHAN ERGOSTEROL - Benhard F Situmorang; Fajar Restuhadi; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The aim of the research was to obtain the best combination treatment between ergosterol concentration and sugar concentration 250 g/l; Tween80 0,2%. Tween80 and ergosterol as surfactant and nutrition for Saccaromyces cerevisiae to produce ethanol on very high gravity fed batch fermentation from Nypa sap. The exploration research used four treatments with duplicate measurements. Treatments consist of E0 (ergosterol 0 mg/l), E1 (ergosterol 18 mg/l), E2 (ergosterol 24 mg/l) and E3 (ergosterol 30 mg/l). Observation was conducted every 24 hours to sugar concentration, ethanol concentration, amount of cell, and pH. The best combination treatment was E1 (Tween80 0.2%; sugar 250 g/l and ergosterol 18 mg/l) which produced ethanol 17,57%.   Keywords: Nypa sap, Tween80, Ergosterol, fed batch, Bioethanol, Very High Gravity Fermentation